Prediktor Burnout Karyawan: Analisis Pengaruh Beban Kerja dan Konflik Peran pada PT. JM Mutu Utama Kantor Pusat BSD Kota Tangerang Selatan - Dela Amanda Fitria; Nuraeni Nuraeni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research is motivated by differences in the results of previous research related to things that affect employee burnout, especially workload and role conflicts. Increasing work demands and unclear roles in organizations make burnout an important problem because it has an impact on employee welfare and performance. Therefore, this study aims to analyze the influence of workload and role conflicts on employee burnout, as well as provide an empirical picture of the dominant factors that contribute to the level of employee burnout in the context of the organization studied. This study uses a quantitative approach with the type of associative research. The sampling technique used saturated sampling with a sample of 80 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with statistical tests. This study provides results that partially workload and role conflicts have a significant effect on employee burnout. These results show that the higher the workload and the more unclear the role that employees play, the level of burnout experienced tends to increase. These findings imply how important workload management and clarity of role are as burnout prevention efforts as well as making theoretical contributions to other variables. Practically, the results of this research can be considered for management in designing more effective work policies to improve employee welfare.